Gastrointestinal Stromal Tumors and Associated Tumors. (15th June 2017) - Kuroiwa, Joshua; Lisanti, Christopher; Smith, Nathaniel; Schwope, Ryan; Walker, Kyle; Bui-Mansfield, Liem T.
Abstract : Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor in the gastrointestinal tract. GISTs are found most commonly in the stomach; followed by the small bowel, colon and rectum, esophagus, and extragastrointestinal tract. On initial staging evaluation of GISTs, the radiologist must determine the organ of origin; size; local invasion; and distant metastases, typically to the liver and peritoneum. If additional lesions are found in other locations, then syndromes related to GISTs must be considered. These include Carney triad, Carney-Stratakis syndrome, neurofibromatosis type 1 (NF1), and familial GIST syndrome. During follow-up imaging, the tasks of the radiologist are to detect residual or recurrent disease, evaluate response to therapy, and identify distant metastases while being vigilant for nonsyndromic metachronous tumors.